ANALISIS DAN PEMODELAN SISTEM INFORMASI PENILAIAN KINERJA DOSEN PADA STIKOM DINAMIKA BANGSA JAMBI - Eriya Eriya; Desi Kisbianty (LPPM STIKOM Dinamika Bangsa, 2014)
In such a competitive and global world as today, every Higher Education needs a professional lecturer who has high performance in an effort to achieve its goals. Therefore, every Higher Education needs to evaluate and assess the performance of the lecturer. STIKOM DB Jambi has not have a standardized system for assessing the performance of employees yet, especially the lecturer. In order to ease the assessment of the lecturer performance, several criteria and standards need to be set out to be used as the assessment guidelines. Thus, to support the information system, systems analysis and systems modeling are conducted by using the object-oriented approach with UML tools. Thus, by the existance of that information systems, STIKOM DB Jambi is helped in doing the assessment quickly and effectively. In addition, it can also improve the quality of teaching and lecturer’s self-development. Keywords: Information Systems, Lecturer Performance, UML